Controle Estoc astico, Backward SDEs e EDPs Parab olicas - Nascimento, Jorge Alexandre Cardoso do (2015)
The Dissertation study the relations between control theory, stochastic calculus and parabolic partial di erential equations. The aim is to study representations of viscosity solutions for parabolic equations via the Feynman-Kac nonlinear formulas. To this end, the control theory plays an important role in the connection between the stochastic and deterministic approaches.